Quality of virtual reality and its impacts on behavioral intention. (September 2020) - Lee, Minwoo; Lee, Seonjeong Ally; Jeong, Miyoung; Oh, Haemoon
Highlights: This is one of the first empirical studies on the impact of the quality factors of virtual reality on behavioral intention in hospitality management. The quality-driven virtual reality research framework is developed based on the DeLone and McLean's IS success model. Content quality, system quality, and vividness positively affect customers' attitude and telepresence, leading to behavioral intention. Research findings help the practitioners better use virtual reality as a promotional destination marketing platform. Abstract: Although virtual reality (VR) has received growing attention and been adopted as customer engagement and marketing tools in the hospitality and tourism industry, little research has been conducted in quality assessment of VR and its impact on customers' psychological acceptance. Building upon the DeLone and McLean's IS success model, this study identifies the quality factors of VR and examines their impacts on customers' behavioral intention. This study develops a quality-driven VR framework and tests the proposed hypotheses assessing customers' behavioral intentions. For the empirical analysis, this study recruits potential U.S. customers and asks them to browse a VR-based destination website and then to answer the online survey related to VR applications. The collected responses are analyzed by PLS-SEM. Findings suggest that content quality, system quality, and vividness positively influence customers' attitude and telepresence, leading to their positive behavioral intention to visit the destination.